ANALISIS PENGARUH PROMOSI, HARGA DAN INOVASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SASIRANGAN MENGGUNAKAN REGRESI LOGISTIK ORDINAL - Dhika Nugraha; Dewi Anggraini; Fuad Muhajirin (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
Purchasing decision is a very important thing to create an optimal marketing plan. Promotion, price and innovation are factors that influence the decision to buy a product. Home industry craftsmen must be able to determine the right strategy to increase consumer purchasing decisions for a product. This is a problem that requires a solution by identifying the factors that influence purchasing decisions for sasirangan fabric in one of the home industries in Kalimantan Province using the ordinal logistic regression analysis method. Ordinal logistic regression analysis is a regression analysis in which the response variable is in the form of categories. The results of this study obtained one significant predictor variable, namely the price variable with the OR value obtained 1322 times. Assessment of the decision making process of buyer interest for the price of Sasirangan products is mostly in the high category, 1322 times compared to the low category